Smoking cessation interventions for smokers diagnosed with cancer: a systematic review. (November 2022) - Frazer, Kate; Bhardwaj, Nancy; Fox, Patricia; Niranjan, Vikram; Stokes, Diarmuid; Quinn, Seamus; Kelleher, Cecily C; Fitzpatrick, Patricia
Abstract: Background: Smoking continuation or uptake after a diagnosis of cancer is associated with decreased treatment efficacy, health deterioration, and worse survival outcomes; nonetheless, many patients with cancer continue smoking after their diagnosis. The extent and effectiveness of smoking cessation services in this cohort is poorly understood, but engagement with smoking cessation services is known to be scarce. The aim of this systematic review was to identify interventions for smokers diagnosed with cancer, as part of a larger study to develop a quit pathway. Methods: We searched PubMed, Embase, PsycInfo, and the Cumulative Index to Nursing and Allied Health Literature database for articles published between Jan 1, 2015, and Dec 15, 2020, in English, reporting an intervention for smokers aged 18 years or older with a diagnosis of lung, breast, cervical, or head and neck cancer (smoking-related cancers), and with no restriction on study design. Outcomes included intervention descriptions and quit rates. Data were independently screened, extracted, and assessed for quality. This systematic review is registered with the International Prospective Register of Systematic Reviews (number CRD42020214204). Findings: 4293 unique records were found, of which 23 studies (nine randomised controlled trials, ten observational studies, three quality improvement studies, and one qualitative study met the inclusion criteria. Studies included between 11 and 2652 participants. 17 (74%) studies reported data from the USA, with the remainder 6 (26%) reporting data from Canada, Australia, Lebanon, and England. Ten (43%) studies reported data from head and neck cancer, three (13%) from lung cancer, one (4%) for breast cancer, and the remaining nine studies (39%) reported combined data for multiple cancers. Duration of smoking cessation interventions ranged between 1 month and 24 months. The heterogeneity of the data prompted a narrative synthesis. Key smoking cessation interventions included long-term use of pharmacotherapy, high tech e-referral systems, national quitting programmes, quitting apps, enhanced counselling, and an opt-out referral system. Four randomised controlled trials and four observational studies reported sustained quit attempts. Factors associated with quitting included timing and frequency of quitting conversations (pre-operatively), extended use of varenicline (up to 24 weeks), and counselling. Patient challenges included pain, fatigue, guilt, and lack of confidence. Interpretation: A multifaceted approach including personalised treatment plans is needed to promote smoking cessation in patients with cancer. Funding: Irish Cancer Society (grant SCA19FIT).